Clinical application of nanopore sequencing for haplotype linkage analysis in preimplantation genetic testing for Duchenne muscular dystrophy - Qiuping Xia; Tianli Chang; Taoli Ding; Zhen Liu; Jiaqi Liu; Yanping Li; Zhongyuan Yao (Scientific Reports)
Abstract Duchenne muscular dystrophy (DMD) is an X-linked recessive disorder characterized by progressive muscular dystrophy, ultimately leading to paralysis and death from cardiac failure and/or respiratory insufficiency. Preimplantation genetic testing for monogenic disorders (PGT-M) has proven effective in helping families with complete pedigrees carrying DMD mutations to produce unaffected offspring. This study was designed to evaluate the feasibility of using nanopore sequencing as an effective PGT-M technique for DMD, particularly in cases involving de novo mutations or incomplete pedigrees that cannot be analyzed using second-generation sequencing (SGS) alone. Nanopore sequencing was performed on two DMD female carriers. The precise breakpoints of the DMD mutations were detected with nanopore sequencing, and haplotypes were constructed based on flanking single-nucleotide polymorphisms (SNPs). Haplotype linkage analyses were subsequently performed by comparing parental SNPs with embryonic SNPs to determine whether the embryos inherited the maternal DMD mutation-carrying chromosome. We successfully identified disease-free euploid embryos for both pedigrees. These results were consistent with the data obtained using SGS and amniocentesis. Our results establish nanopore sequencing as a clinically applicable methodology for preimplantation haplotype linkage analysis in PGT-M for DMD, particularly valuable for families with non-informative pedigrees where traditional linkage analyses are not feasible. This finding is crucial for reducing the propagation of DMD in the population through the application of nanopore sequencing.